Synchronization of Legislation on Narcotics Abuse by Civil Servants from the Perspective of General Principles of Good Governance - Hikmal, Andi; Muhjad, Hadin; Brata, Trisna Agus Brata (Kirana Publisher (KNPub), 2025)
This study aims to analyse the synchronisation of regulations concerning the dismissal and reinstatement of Civil Servants (PNS) involved in narcotics-related criminal offences, by examining the alignment between Government Regulation (PP) Number 94 of 2021 on Civil Servant Discipline and the Regulation of the Head of the National Civil Service Agency (BKN) Number 3 of 2020 on Technical Guidelines for the Dismissal of Civil Servants. The study employs a normative legal research method with a statutory approach and the general principles of good governance (AUPB). The findings reveal a lack of harmony between these two regulations, as PP 94/2021 stipulates dismissal as a severe disciplinary sanction for civil servants involved in drug abuse, whereas BKN Regulation 3/2020 allows for reinstatement under certain conditions. This inconsistency has the potential to create legal uncertainty and opens the door for subjectivity in the implementation of civil service policies. To ensure legal certainty, this study recommends regulatory harmonisation through a revision of BKN Regulation 3/2020 to align more closely with PP 94/2021. Furthermore, there is a need for stricter standard operating procedures (SOPs), a transparent oversight mechanism, and enhanced capacity-building for personnel management officials in applying the principles of good governance. These measures are expected to ensure legal certainty while supporting a more professional and integrity-driven bureaucratic reform.